Optimization of the magnetic core of a Linear Variable Differential Transducer - Van Nieuwenhove Rudi (EPJ Web of Conferences, 2023)
Research into materials and fuels for nuclear power reactors is carried out in so-called research reactors where various types of fuels and materials can be monitored online and in real time by in-core instruments. At the Halden reactor in Norway, online measurements such as cladding elongation, inner fuel rod pressure, fuel swelling, material creep and stress relaxation were based on Linear Variable Differential transducers (LVDT). The magnetic core of the standard LVDT core is made of silicon iron, encapsulated by an Inconel 600 or AISI 316L tube for corrosion protection. In the present study, we consider FeCrAl as magnetic core material. This material, which is currently also being investigated as accident tolerant fuel cladding material, is corrosion resistant in the chemical environment of PWR or BWR reactors and therefore doesn’t required an extra corrosion protection tube. As a result, the magnetic core diameter can be made larger, resulting in an increase of the LVDT sensitivity. In order to verify the various dependencies, the LVDT sensitivity was measured and compared to finite element calculations. The sensitivity of an LVDT is influenced by the magnetic permeability of the magnetic core, as well as by eddy current losses in this magnetic core. When the temperature changes, the eddy current losses in the core also change, resulting in a slight change of the LVDT sensitivity. It is shown that this effect is reduced when using FeCrAl as magnetic core material, instead of SiFe. On the other hand, the change in magnetic permeability with temperature for FeCrAl is larger than for SiFe. The overall combined effect results in a higher dependence of sensitivity for the FeCrAl core. Finally, using a solid magnetic core (without encapsulation) allows operation of the LVDT at higher gamma heating in the core of a reactor because of improved cooling by the surrounding water. This feature is relevant for operation in the Jules Horowitz Reactor, where the gamma heating in some locations can be up to 20 W/g.